Determination of Oriental Tradeware Ceramics: A proposed system for identifying and documenting pottery in Philippine archaeological sites - Melendres, Rhayan G. (Hukay, 2014)
There is a need to improve on the practice of analysing oriental tradeware ceramics found in Philippine archaeological sites. The current practices mostly depend on authority and the process of identification is not presented. Oriental tradeware ceramics, in this study, are defined as the porcelain and stoneware that originated from Asia specifically from the current nation states of China, Thailand, Vietnam and Burma. The first part of the paper is a review of oriental tradeware studies done in the Philippines as well as their documentation. Then, this research proposes a determination system for excavated oriental tradeware ceramics composed of two parts: identification and documentation. Reporting the cross referencing of available ceramic data and stating the level of confidence of the identification are some of the new steps added in this oriental tradeware ceramics determination system. Then, the database shall be encoded into a digital form for documentation.